Studying the Behavior of Asphalt Stabilized Gepseous Soil for Earth Embankment Model (Journal of Engineering, 2014)
The study presents the test results of stabilizing gypseous soil embankment obtained fromAl- Faluja university Campus at Al-Ramady province. The laboratory investigation was dividedinto three phases, The physical and chemical properties, the optimum liquid asphalt (emulsion)requirements (which are manufactured in Iraq) were determined by using one dimensionalunconfined compression strength test.in the first phase , The optimum fluid content was 11%(6% of emulsion with 5% water content).. At phase two, the effect of Aeration technique wasinvestigated using both direct shear and permeability test. At phase three for the case of staticload , the pure soil embankment model under dry test condition was investigated, The testingprogram included the determination of the unconfined compressive strength, direct shearstrength, constant head permeability test, and one dimensional consolidation test for pure andasphalt stabilized gypseous soil. Testing was carried out in dry and absorbed conditions, themaximum pressure that can be supported before failure (ultimate sustained pressure) is 0.76MPa with vertical settlement (0.21 mm) . However, For the pure soil embankment model underabsorbed condition it was found that the maximum pressure before failure (ultimate sustainedpressure) is 0.3 MPa with vertical settlement (12 mm), Which reflects the reduction in bearingcapacity by (61%). Compression was made for absorbed stabilized soil and un-absorbed soiltested under hydraulic conductivity test for seven days, the results showed that a very lowmargin deffeneces in maximum pressure resistance and settlement were obtained (4.38 MPa ,0.11mm ) and (4.11MPa , 0.12mm).